Socio-demographic Status and Mode of Transmission of Avian Influenza among Poultry Farm Workers (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Avian influenza is considered as serious global public health problem for poultry industry. Literature suggests that when HPAI/H5N1 Avian influenza (AI) outbreaks, humans are prone to increased risk of transmission. The recent pandemic caused by highly pathogenic AIA (H5N1) in domestic poultry is currently rated phase-3 by the World Health Organization on the pandemic alert scale. Every year 244 species of migratory birds visit Bangladesh in the winter season (October-March) of which approximately 21 species may carry the H5N1 or HPAI (Highly Pathogenic Avian influenza) virus.Objective: To assess socio demographic status and knowledge on mode of transmission of avian influenza among the poultry workers of selected poultry farms in Dhaka city.Materials and Methods: This was a cross-sectional study carried out among the poultry workers of selected poultry farms in Dhaka city. The study was conducted over a period of six months from January 2008 to June 2008. A total of 150 poultry workers aged 9 years and above irrespective of sexes were interviewed face to face by using semi-structured questionnaire.Results: Majority of the respondents were male (92%) and nearly 78% of the respondents had educational level from Class-V to SSC. About three fourth of the respondents (68%) mentioned that avian influenza was transmitted by direct contact. Eighty percent (80%) of the respondents had the knowledge on transmission from poultry to human whereas 63% had the knowledge on transmission from human to human. Good, fair and poor knowledge on mode of transmission of avian influenza was found in 21.33%, 42.67% and 36% of the subjects respectively. Among the respondents belonging to